Evaluating the Doctrine of Command Responsibility under International Criminal Law : Its Suitability in the Prosecution of Conflict-Related Sexual Violence Crimes - Tladi, Dire (University of Pretoria, 2023)
Thesis (LLD)--University of Pretoria, 2023.